Slack K+ channels attenuate NMDA‐induced excitotoxic brain damage and neuronal cell death. Issue 5 (5th April 2021) - Ehinger, Rebekka; Kuret, Anna; Matt, Lucas; Frank, Nadine; Wild, Katharina; Kabagema‐Bilan, Clement; Bischof, Helmut; Malli, Roland; Ruth, Peter; Bausch, Anne E.; Lukowski, Robert
Abstract: The neuronal Na + ‐activated K + channel Slack ( aka Slo2.2, KNa 1.1, or Kcnt1 ) has been implicated in setting and maintaining the resting membrane potential and defining excitability and firing patterns, as well as in the generation of the slow afterhyperpolarization following bursts of action potentials. Slack activity increases significantly under conditions of high intracellular Na + levels, suggesting this channel may exert important pathophysiological functions. To address these putative roles, we studied whether Slack K + channels contribute to pathological changes and excitotoxic cell death caused by glutamatergic overstimulation of Ca 2+ ‐ and Na + ‐permeable N ‐methyl‐D‐aspartic acid receptors (NMDAR). Slack‐deficient (Slack KO) and wild‐type (WT) mice were subjected to intrastriatal microinjections of the NMDAR agonist NMDA. NMDA‐induced brain lesions were significantly increased in Slack KO vs WT mice, suggesting that the lack of Slack renders neurons particularly susceptible to excitotoxicity. Accordingly, excessive neuronal cell death was seen in Slack‐deficient primary cerebellar granule cell (CGC) cultures exposed to glutamate and NMDA. Differences in neuronal survival between WT and Slack KO CGCs were largely abolished by the NMDAR antagonist MK‐801, but not by NBQX, a potent and highly selective competitive antagonist of α‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazolepropionic acid (AMPA)‐type ionotropic glutamate receptors. Interestingly, NMDAR‐evoked Ca 2+ signals did not differ with regard to Slack genotype in CGCs. However, real‐time monitoring of K + following NMDAR activation revealed a significant contribution of this channel to the intracellular drop in K + . Finally, TrkB and TrkC neurotrophin receptor transcript levels were elevated in NMDA‐exposed Slack‐proficient CGCs, suggesting a mechanism by which this K + channel contributes to the activation of the extracellular‐signal‐regulated kinase (Erk) pathway and thereby to neuroprotection. Combined, our findings suggest that Slack‐dependent K + signals oppose the NMDAR‐mediated excitotoxic neuronal injury by promoting pro‐survival signaling via the BDNF/TrkB and Erk axis.